Differentiation-Dependent Motility-Responses of Developing Neural Progenitors to Optogenetic Stimulation - Köhidi, Tímea; Jády, Attila G.; Markó, Károly; Papp, Noémi; Andrási, Tibor; Környei, Zsuzsanna; Madarász, Emília (Frontiers in Cellular Neuroscience, 2017)
During neural tissue genesis, neural stem/progenitor cells are exposed to bioelectric stimuli well before synaptogenesis and neural circuit formation. Fluctuations in the electro-chemical potential in the vicinity of developing cells influence the genesis, migration and maturation of neuronal precursors. The complexity of the in vivo environment and the coexistence of various progenitor populations hinder the understanding of the significance of ionic/bioelectric stimuli in the early phases of neuronal differentiation. Using non-invasive optogenetic stimulation, we investigated the in vitro motility responses of radial glia-like neural stem/progenitor populations to ionic stimuli. Radial glia-like neural stem cells were isolated from CAGloxpStoploxpChR2(H134)-eYFP transgenic mouse embryos. After transfection with Cre-recombinase, ChR2-expressing and non-expressing cells were separated by eYFP fluorescence. Expression of light-gated ion channels were checked by patch clamp and fluorescence-intensity assays. Neurogenesis by ChR2-expressing and non-expressing cells was induced by withdrawal of EGF from the medium. Cells in different (stem cell-, migrating progenitor- and maturing precursor) stages of development were illuminated with laser light (λ=488 nm; 1.3mW/mm2; 300 ms) in every 5 minutes for 12 hours. The displacement of the cells was analysed on images taken at the end of each light-pulse. Results demonstrated that the migratory activity decreased with the advancement of neuronal differentiation regardless of stimulation. Light-sensitive cells, however, responded on a differentiation-dependent way. In non-differeniated ChR2-expressing stem cell populations, the motility did not change significantly in response to light-stimulation. The displacement activity of migrating progenitors was enhanced, while the motility of differentiating neuronal precursors was markedly reduced by illumination.